Autoimmune hypophysitis secondary to therapy with immune checkpoint inhibitors: Four cases describing the clinical heterogeneity of central endocrine dysfunction. (October 2020) - Hartmann, Amelie; Paparoupa, Maria; Volkmer, Bjoern G; Rompel, Rainer; Wittig, Andreas; Schuppert, Frank
Introduction: Immune checkpoint inhibitors are becoming increasingly important in oncology. Immune-related adverse events, including autoimmune hypophysitis, have been reported before. Case report: We present a case series of three males and one female, suffering from either malignant melanoma or renal cell carcinoma, who developed hypophysitis under Nivolumab and/or Ipilimumab. A wide range of clinical manifestations from asymptomatic hypophysitis, headache, general weakness, loss of appetite, visual field impairment, and confusion to acute life-threatening Addison crisis was observed. Management and outcome: All patients received corticosteroids. Immune checkpoint inhibitors were discontinued in three cases until resolution of symptoms. Discussion: The objective of our report is to raise the awareness of physicians, regarding this rare clinical entity, which may become life-threatening, if not promptly recognized and properly treated.